FIGURE 1. Camptocercus streletskayae Smirnov, 1998 in Morphology and phylogenetic position of three species of genus Camptocercus Baird, 1843 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zenodo, 2015)
FIGURE 1. Camptocercus streletskayae Smirnov, 1998, parthenogenetic female from Russia, Chukotka, a puddle in the region of the Anadyr River. A, lateral view. B–C, ventral margin of valve (posterior and anterior part of same valve). D–F, posteroventral angle of valve. G, head. H, head pores. I–J, postabdomen. K–L, distal portion of postabdomen. M, postabdominal claw. N, basal spine of postabdominal claw. O, antennule. P. antenna. Published as part of Sinev, Artem Y., 2015, Morphology and phylogenetic position of three species of genus Camptocercus Baird, 1843 (Cladocera: Anomopoda: Chydoridae), pp. 169-186 in Zootaxa 4040 (2) on page 172, DOI:10.11646/zootaxa.4040.2.4, http://zenodo.org/record/233695